2010
DOI: 10.3109/09637481003691820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roasting on oil and fatty acid composition of Turkish hazelnut varieties (Corylus avellanaL.)

Abstract: A total of 18 natural and roasted hazelnut varieties (namely, Aci, Cavcava, Cakildak, Foşa, Ham, Incekara, Kalinkara, Kan, Karafindik, Kargalak, Kuş, Mincane, Palaz, Sivri, Tombul, Uzunmusa, Yassi Badem, and Yuvarlak Badem), grown in the Giresun province of Turkey, were compared for their differences in oil content and fatty acid profiles. The oil content in natural and roasted hazelnut varieties ranged from 57.85% for Kargalak to 68.31% for Incekara and from 61.37% for Kargalak to 71.72% for Incekara, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 18 publications
7
79
1
Order By: Relevance
“…Yoshida and Takagi (1997) roasted sesame seeds (Sesamum indicum L.) at 160, 180, 200, 220 and 250°C and each for 5, 10, 15, 20 and 25 min; the oil yields increased with roasting temperature and duration. Alasalvar et al (2010) also found that roasting could enhance oil level in Turkish hazelnut varieties (Corylus avellana L.). Our study showed that the oil yields of the almond kernels roasted at 150 or 180°C for 5-20 min increased with roasting temperature and duration.…”
Section: Samplementioning
confidence: 95%
See 2 more Smart Citations
“…Yoshida and Takagi (1997) roasted sesame seeds (Sesamum indicum L.) at 160, 180, 200, 220 and 250°C and each for 5, 10, 15, 20 and 25 min; the oil yields increased with roasting temperature and duration. Alasalvar et al (2010) also found that roasting could enhance oil level in Turkish hazelnut varieties (Corylus avellana L.). Our study showed that the oil yields of the almond kernels roasted at 150 or 180°C for 5-20 min increased with roasting temperature and duration.…”
Section: Samplementioning
confidence: 95%
“…Roasting treatment increased the fatty acid content in walnut oil (Kita & Figiel, 2007). Alasalvar et al (2010) reported that roasting had minor influence on fatty acid profile of Turkish hazelnut varieties (Corylus avellana L.). After roasting at 180°C for 20 min, the level of saturated fatty acids slightly increased in kulthi (Dolichos biflorus) seeds, but unsaturated fatty acids had opposite result (Mishra and Pathan, 2011).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that roasting the seeds did not affect the fatty acid composition of the mustard seed oil. It was reported that the fatty acid composition did not change with roasting in sesame seeds [25] or in hazelnuts [26].…”
Section: Initial Characteristics Of Mustard Seed Oilsmentioning
confidence: 99%
“…Few studies about the fatty acid composition and tocopherol level changes during the roasting process of hazelnuts have already been reported (Amaral et al 2006;Alasalvar et al 2010), however, the roasting of hazelnut varieties grown in Poland has not been studied at all, to our knowledge. The objectives of this study was to assess the oxidative stability of roasted hazelnuts using PDSC methodology combined with more common fatty acids and tocopherol determinations and middle FT-IR (MID-FT-IR) spectroscopy analysis referred to classic quality oil assessments.…”
Section: Introductionmentioning
confidence: 99%